Muckle–Wells syndrome: clinical perspectives - Tran TA (Dove Medical Press, 2017)
Tu-Anh Tran Department of Pediatrics, Nîmes University Hospital, INSERM U1183, Montpellier-Nîmes University, Nîmes, France Abstract: Muckle–Wells syndrome (MWS) is a rare autoinflammatory disorder. It is due to NLRP3 gene mutations, responsible for excessive caspase-1 activation and interleukin 1β processing. MWS is the intermediate phenotype of severity of cryopyrin-associated periodic syndrome. Urticarial rash, conjunctivitis, recurrent fever, arthralgia, and fatigue are the main clinical manifestations of MWS. Yet, sensorineural hearing loss and renal amyloidosis can occur after long term evolution. Patients’ quality of life has been drastically improved with the advent of IL-1 inhibitors. This review reports recent findings in MWS, particularly genotype/phenotype correlation, and discusses the clinical perspectives of this disease in a time of efficient treatment. Keywords: Muckle–Wells syndrome, anti-interleukin 1, anakinra, rilonacept, canakinumab, clinical presentation, cryopyrin-associated periodic syndrome, CAPS, NLRP3 gene